Vaccination and Mortality of Patients with a Novel Coronavirus Infection (COVID-19): A Global Approach - N. A. Benuni; A. S. Kotusov; F. S. Adzhieva; A. E. Kucher; K. A. Tolmacheva; V. N. Dushuk; R. V. Maslennikov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The aim is to study the correlation between the vaccination rate (VR) and mortality rate of patients with COVID-19 (MpCOV).Methods. The countries with gross domestic product per capita corrected for purchasing power parity (GDP PPP) over $-10,000 were selected for an ecologic study. The city-states and countries with a population of 1,000,000 were excluded. The number of patients who died from COVID-19 within a week was divided by the number of patients diagnosed with COVID-19 within a week 20 days earlier to calculate MpCOV.Results. We included 85 countries. VR (r = –0.604; p < 0.001) and GDPpcPPP level (p = 0.202), is an independent determinant of MpCOV. There was no significant difference in MpCOV between groups of countries with VR < 20 % and 20–39 % (1.96 [1.21; 4.67] vs. 1.96 [1.01; 3.36] %; p = 0.464). MpCOV was higher in countries where VR were lower when groups of countries with VR of 20–39 %, 40–59 %, 60–79 %, and ≥80 % were compared (1.96 [1.01; 3.36] vs. 1.11 [0.76; 1.64] vs. 0.50 [0.39; 1.00] vs. 0.16 [0.10; 0.21]; p = 0.003; p = 0.020, and p = 0.008).Conclusions. An increase in VR correlates with a decrease in MpCOV.